THE SEMIOTICS OF DIVINITY AND RESILIENCE: DECIPHERING DISASTER MITIGATION WISDOM IN THE VERNACULAR ARCHITECTURE OF GHUMAH BAGHI - Reza Aprianti; Rafail Hasanov (Senarai: Journal of Islamic Heritage and Civilization, 2026)
Traditional vernacular architecture often embodies a sophisticated synthesis of spiritual values and environmental adaptation. This study examines the Ghumah Baghi, a traditional house of the Besemah people in South Sumatra, which has survived centuries of seismic activity. While previous studies focused on its physical structure, there is a lack of research integrating its theological symbolism with disaster mitigation functions. This research employs a qualitative method with a semiotic approach, utilizing Peirce’s triadic model to analyse the meanings behind the architectural ornaments and structural systems. The findings reveal that the divine symbols in Ghumah Baghi-such as the Tiang Duduk (floating foundation) and floral carving-represent a “theology of balance” between humans, nature, and the Creator. Critically, these spiritual symbols manifest that advanced indigenous engineering; the non-fixed foundation serves as a base-isolation system that provides seismic resilience. The study concludes that the theological philosophy of “yielding to divine nature” is the fundamental driver behind the building’s structural endurance. This research contributes to the discourse of ethno-architecture by proving that local wisdom and spiritual semiotics are essential components in developing sustainable and culturally-rooted disaster mitigation strategies.